Gender Differences in STEM Education : A Review Study - Pathak, Bhawani (Sotang, Yearly Peer Reviewed Journal, 2022)
The low participation of females in STEM (Science, Technology, Engineering, and Mathematics) subjects is a worldwide issue. There are so many problems being raised in the context of studying higher education for females. The purpose of this study is to explore the effecting factors in enrollment and success in STEM education for females. It is based on the review of literature on female enrollment and participation in STEM education. Due to several factors such as stereotypes and biases, societal and cultural misconceptions, lack of confidence and self-perception, and gender-based discrimination are the major causes to enhance the gender gap in STEM education. To create a more inclusive environment for females in STEM education the role of nation, society, and family is to be supportive. Women should fight against all kinds of discrimination based on their willpower. This study would help to empower women and also contribute to investigate the cause of gender inequality in STEM education and enhancing gender equality. This study can be important for states and organizations to make policies and plans to improve the education status of women in STEM education.